2005
DOI: 10.1002/jmv.20434
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of chronic HBV infection: A cohort study with up to 12 years follow-up in North Greece (part of the Interreg I-II/EC-project)

Abstract: The aim of the study was to assess the long-term outcome of chronic hepatitis B surface antigen (HBsAg) carriers in the general population in North Greece (Thrace), an area with an intermediate endemicity. This was a part of the Interreg I-II EC project. Two hundred sixty three chronic HBsAg+ carriers, median age 34 years (20-65), were evaluated prospectively for a median follow-up of 5 years (2-12). Hepatitis B virus (HBV) markers and ALT were examined every 6 months and serum HBV-DNA every 12 months. Liver b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
64
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 51 publications
8
64
2
2
Order By: Relevance
“…This is in line with observations made in other studies that reported that there are few patients who recall their acute episode of hepatitis, making it likely that intrafamily acquisition of the virus in the first years of life is the most common form of transmission of HBeAg-negative disease [5,19].…”
Section: Clinico-epidemiological Manifestationssupporting
confidence: 90%
“…This is in line with observations made in other studies that reported that there are few patients who recall their acute episode of hepatitis, making it likely that intrafamily acquisition of the virus in the first years of life is the most common form of transmission of HBeAg-negative disease [5,19].…”
Section: Clinico-epidemiological Manifestationssupporting
confidence: 90%
“…Compared with the results of a few earlier studies, [3][4][5][6] these figures are obviously much higher (Fig. 1).…”
contrasting
confidence: 63%
“…1 This finding is also contradictory to earlier observations: abnormal ALT level was observed between the third and twelfth month of follow-up in all 25 HBeAg-negative subjects with normal baseline ALT but higher HBV-DNA level 5 ; the only 4 subjects with serum HBV-DNA Ͼ10 4 copies/mL at presentation in another study all exhibited ALT elevation during follow-up. 6 We recently followed 1241 asymptomatic HBeAg-negative HBsAg carriers with PNALT for 14,484 person-years and found that the cumulative probability of hepatitis relapse was 5% at the 2-year follow-up and 10% at the 5-year follow-up. 8 Given these findings in earlier studies and the finding that 16% of Lin's patients had an HBV-DNA level Ͼ10 6 and 32% had a level Ͼ10 5 copies/mL, it is anticipated that the dynamic interaction between the host and HBV in these patients would result in elevated ALT level during follow-up.…”
mentioning
confidence: 99%
“…Previous studies reported an HBeAg positivity rate of 2.5% to 29.4% (10,(13)(14)(15) studies was 10.5% (10), 13.3% (16), 30% (17), and 10% (18). Seroconversion is affected by factors, such as precore mutation, the phase of hepatitis, and the age when afflicted by HBV infection.…”
Section: Discussionmentioning
confidence: 95%